An ergonomic evaluation and intervention of the computer workstation among the office staff in an engineering - Sahu, Mona; Prabhu Rubesh, G.; Jayaseelan, P. (International Journal of Engineering and Technology, 2018)
As the office automation increases, the use of computer workstations is swiftly growing. Regardless of its several benefits, work-related risks such as eye strain and musculoskeletal stresses have developed as a significant problem. This analysis was designed to investigate the effects of work postures upon the musculoskeletal stresses experienced by the computer tasks operators in Karunya Institute of Technology and Sciences. A survey is done using the Occupational Safety and Health Administration evaluation checklist and an evaluation checklist prepared by â€˜Rauf Iqbalâ€™ in order to gather information on the issues like work practice, workstation, and health-related issues on the users. A detailed analysis of the body posture of 20 employees was done using the tool Rapid Upper Limb Assessment (RULA). The results of the checklistâ€™s and RULA were analyzed to identify the specific problems faced by the computer users. Based on the specific problems identified, changes in the workstation were proposed. RULA analysis was conducted again on the redesigned workstations and results were compared. It was concluded that this ergonomic analysis helped to identify the reason for discomfort and implement relevant changes in order to reduce the discomfort level of the subjects in the different office section. Â